Activated mutant forms of PIK3CA cooperate with RasV12 or c‐Met to induce liver tumour formation in mice via AKT2/mTORC1 cascade. (30th January 2016) - Wang, Chunmei; Che, Li; Hu, Junjie; Zhang, Shanshan; Jiang, Lijie; Latte, Gavinella; Demartis, Maria I.; Tao, Junyan; Gui, Bing; Pilo, Maria G.; Ribback, Silvia; Dombrowski, Frank; et al.
Abstract: Background & Aims: Activating mutations of PIK3CA occur in various tumour types, including human hepatocellular carcinoma. The mechanisms whereby PIK3CA contributes to hepatocarcinogenesis remain poorly understood. Methods: PIK3CA mutants H1047R or E545K were hydrodynamically transfected, either alone or in combination with NRasV12 or c‐Met genes, in the mouse liver. Results: Overexpression of H1047R or E545K alone was able to induce AKT/mTOR signalling in the mouse liver, leading to hepatic steatosis. However, none of the mice developed liver tumours over long term. In contrast, H1047R or E545K cooperated with NRasV12 or c‐Met to rapidly induce liver tumour formation in mice. At the molecular level, all the tumour nodules displayed activation of AKT/mTOR and Ras/MAPK cascades. Ablation of AKT2 significantly inhibited hepatic steatosis induced by H1047R or E545K and carcinogenesis induced by H1047R/c‐Met or E545K/c‐Met. Furthermore, tumourigenesis induced by H1047R/c‐Met was abolished in conditional Raptor knockout mice. Conclusions: Both H1047R and E545K are able to activate the AKT/mTOR pathway. An intact AKT2/mTOR complex 1 cascade is required for tumourigenesis induced by H1047R/c‐Met or E545K/c‐Met in the liver.